Chronic Unpredictable Mild Stress Promotes Atherosclerosis via HMGB1/TLR4-Mediated Downregulation of PPARγ/LXRα/ABCA1 in ApoE-/- Mice - Gu, Hong-Feng; Li, Na; Xu, Zhao-Qian; Hu, Lu; Li, Hui; Zhang, Rong-Jie; Chen, Ru-Meng; Zheng, Xi-Long; Tang, Ya-Ling; Liao, Duan-Fang (Frontiers in Physiology, 2019)
Background: Although our previous studies have confirmed that the activation of TLR4 is implicated in the development of atherosclerosis induced by chronic unpredicted mild stress (CUMS), the underling mechanism is largely unclear. Here, we hypothesized that CUMS accelerates atherosclerotic development through lowering PPARγ/LXRα-ABCA1 expression via HMGB1/TLR4 signaling. Methods: In present study, CUMS atherosclerotic animal models were established with AopE-/- mice, and CUMS Raw 264.7 macrophage models were mimicked by high corticosterone treatment，These models were treated with Ethyl pyruvate (EP, an inhibitor of HMGB1), TLR4 inhibitor TAK-242, and PPARγ agonist (Rosiglitazone, RSG) to test our hypothesis, respectively. Results: Our results indicated that the protein levels of HMGB1, TLR4, and pro-inflammatory cytokines including IL-1β, TNF-α were elevated with the development of atherosclerosis in CUMS mice, while the expressions of PPARγ, LXRα, and ABCA1 declined. Notably, HMGB1 inhibition by EP reversed CUMS-induced atherosclerotic development, pro-inflammatory cytokines upregulation, and PPARγ/LXRα-ABCA1 downregulation. The same trend was observed in the stressed mice treatment with TAK-242. Further experimental evidences indicated that EP, TAK-242, and RSG treatment notably corrected foam cell formation, HMGB1 release, and drown-regulation of LXRα and ABCA1 in CUMS Raw 264.7 macrophage model. Conclusion: These results indicate that CUMS exacerbates atherosclerosis is likely via HMGB1-mediated downregulation of PPARγ/LXRα-ABCA1 through TLR4. These data reveal a novel mechanism by which CUMS aggravates atherosclerosis and may offer a potential therapeutic target for this disease.